CRISPR-Cas9-mediated insertion of a short artificial intron for the generation of conditional alleles in mice - Annelise Cassidy; Stephane Pelletier (STAR Protocols, 2023)
Summary: In this protocol, we describe the generation of conditional alleles in mice using the DECAI (DEgradation based on Cre-regulated Artificial Intron) approach. We detail steps for the CRISPR-mediated insertion of the short DECAI cassette within exon 3 of Scyl1 and the functional validation of alleles at genomic, transcriptomic, and protein levels. This strategy simplifies the process of generating mice with conditional alleles.For complete details on the use and execution of this protocol, please refer to Cassidy et al. (2022).1 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.